# Question and Answers Forum

None Questions

Question Number 139296 by mohammad17 last updated on 25/Apr/21

$$\int_{\mathrm{0}} ^{\:\mathrm{1}} \frac{\sqrt{{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx} \\$$

Answered by qaz last updated on 25/Apr/21

$$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx}=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{\mathrm{1}−{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\mathrm{1}} {dx}=\frac{\mathrm{1}}{\mathrm{2}} \\$$

Commented by mohammad17 last updated on 25/Apr/21

$${sir}\:{how} \\$$$$\\$$$$\int_{\mathrm{0}} ^{\:\mathrm{1}} \frac{\sqrt{{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx}=\int_{\mathrm{0}} ^{\:\mathrm{1}} \frac{\sqrt{\mathrm{1}−{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx} \\$$

Commented by Ar Brandon last updated on 25/Apr/21

$$\int_{\mathrm{a}} ^{\mathrm{b}} \mathrm{f}\left(\mathrm{x}\right)\mathrm{dx}=\int_{\mathrm{a}} ^{\mathrm{b}} \mathrm{f}\left(\mathrm{a}+\mathrm{b}−\mathrm{x}\right)\mathrm{dx} \\$$$$\mathcal{I}=\begin{cases}{\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}\mathrm{dx}}\\{\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{\mathrm{1}−\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}\mathrm{dx}}\end{cases} \\$$$$\Rightarrow\mathrm{2}\mathcal{I}=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}\mathrm{dx}=\int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{dx}=\mathrm{1} \\$$$$\Rightarrow\mathcal{I}=\frac{\mathrm{1}}{\mathrm{2}} \\$$

Commented by mr W last updated on 25/Apr/21

$${let}\:{x}=\mathrm{1}−{u} \\$$$$\mathrm{1}−{x}={u} \\$$$${dx}=−{du} \\$$$${x}=\mathrm{0}\:\Rightarrow{u}=\mathrm{1} \\$$$${x}=\mathrm{1}\:\Rightarrow{u}=\mathrm{0} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx}=−\int_{\mathrm{1}} ^{\mathrm{0}} \frac{\sqrt{\mathrm{1}−{u}}}{\:\sqrt{{u}}+\sqrt{\mathrm{1}−{u}}}{du} \\$$$$\:\:\:\:\:\:\:\:\:\:=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{\mathrm{1}−{u}}}{\:\sqrt{{u}}+\sqrt{\mathrm{1}−{u}}}{du} \\$$$$\:\:\:\:\:\:\:\:\:\:=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\sqrt{\mathrm{1}−{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx} \\$$

Answered by Mathspace last updated on 25/Apr/21

$${I}=\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\sqrt{{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx}\:\Rightarrow \\$$$${I}=_{\sqrt{{x}}={t}} \:\:\:\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{{t}}{\:\sqrt{\mathrm{1}−{t}^{\mathrm{2}} }+{t}}\left(\mathrm{2}{t}\right){dt} \\$$$$=\mathrm{2}\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{{t}^{\mathrm{2}} }{{t}+\sqrt{\mathrm{1}−{t}^{\mathrm{2}} }}{dt}\:=_{{t}={siny}} \\$$$$\mathrm{2}\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{2}}} \:\:\frac{{sin}^{\mathrm{2}} {y}}{{siny}+{cosy}}\left({cosy}\right){dy} \\$$$$=_{{tan}\left(\frac{{y}}{\mathrm{2}}\right)={z}} \:\:\:\mathrm{2}\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{4}{z}^{\mathrm{2}} }{\left(\mathrm{1}+{z}^{\mathrm{2}} \right)^{\mathrm{2}} }.\frac{\mathrm{1}−{z}^{\mathrm{2}} }{\mathrm{1}+{z}^{\mathrm{2}} }×\frac{\mathrm{1}}{\frac{\mathrm{2}{z}}{\mathrm{1}+{z}^{\mathrm{2}} }+\frac{\mathrm{1}−{z}^{\mathrm{2}} }{\mathrm{1}+{z}^{\mathrm{2}} }}\frac{\mathrm{2}{dz}}{\mathrm{1}+{z}^{\mathrm{2}} } \\$$$$=\mathrm{4}\:\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{4}{z}^{\mathrm{2}} \left(\mathrm{1}−{z}^{\mathrm{2}} \right)}{\left(\mathrm{1}+{z}^{\mathrm{2}} \right)^{\mathrm{3}} }×\frac{{dz}}{\mathrm{2}{z}+\mathrm{1}−{z}^{\mathrm{2}} } \\$$$$=\mathrm{16}\:\int_{\mathrm{0}} ^{\infty} \:\:\:\frac{{z}^{\mathrm{2}} −{z}^{\mathrm{4}} }{\left(−{z}^{\mathrm{2}} \:+\mathrm{2}{z}+\mathrm{1}\right)\left({z}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{3}} }{dz} \\$$$$=\mathrm{16}\int_{\mathrm{0}} ^{\infty} \:\:\frac{{z}^{\mathrm{4}} −{z}^{\mathrm{2}} }{\left({z}^{\mathrm{2}} −\mathrm{2}{z}−\mathrm{1}\right)\left({z}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{3}} }{dx} \\$$$${let}\:{decompose} \\$$$${F}\left({z}\right)=\frac{{z}^{\mathrm{4}} −{z}^{\mathrm{2}} }{\left({z}^{\mathrm{2}} −\mathrm{2}{z}−\mathrm{1}\right)\left({z}^{\mathrm{2}\:} +\mathrm{1}\right)^{\mathrm{3}} } \\$$$$=\frac{{a}}{{z}−{z}_{\mathrm{1}} }+\frac{{b}}{{z}−{z}_{\mathrm{2}} }\:+\frac{{az}+{b}}{{z}^{\mathrm{2}} \:+\mathrm{1}}+\frac{{mz}+{n}}{\left({z}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{2}} }+\frac{{ez}+{f}}{\left({z}^{\mathrm{2}} \:+\mathrm{1}\right)^{\mathrm{3}} } \\$$$$...{be}\:{conginued}... \\$$

Answered by MJS_new last updated on 25/Apr/21

$$\int\frac{\sqrt{{x}}}{\:\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}}{dx}= \\$$$$\:\:\:\:\:\left[{t}=\frac{\sqrt{\mathrm{1}−{x}}}{\:\sqrt{{x}}}\:\rightarrow\:{dx}=−\mathrm{2}\sqrt{\mathrm{1}−{x}}\sqrt{{x}^{\mathrm{3}} }{dt};\:{x}=\frac{\mathrm{1}}{{t}^{\mathrm{2}} +\mathrm{1}}\right] \\$$$$=−\mathrm{2}\int\frac{{t}}{\left({t}+\mathrm{1}\right)\left({t}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }{dt}= \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int\left(\frac{{t}^{\mathrm{2}} −\mathrm{2}{t}−\mathrm{1}}{\left({t}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }−\frac{{t}}{{t}^{\mathrm{2}} +\mathrm{1}}+\frac{\mathrm{1}}{{t}+\mathrm{1}}\right){dt}= \\$$$$... \\$$$$=−\frac{{t}−\mathrm{1}}{\mathrm{2}\left({t}^{\mathrm{2}} +\mathrm{1}\right)}−\frac{\mathrm{1}}{\mathrm{4}}\mathrm{ln}\:\left({t}^{\mathrm{2}} +\mathrm{1}\right)\:+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}\:\left({t}+\mathrm{1}\right)\:= \\$$$$=−\frac{{t}−\mathrm{1}}{\mathrm{2}\left({t}^{\mathrm{2}} +\mathrm{1}\right)}+\frac{\mathrm{1}}{\mathrm{4}}\mathrm{ln}\:\frac{\left({t}+\mathrm{1}\right)^{\mathrm{2}} }{{t}^{\mathrm{2}} +\mathrm{1}}\:= \\$$$$=\frac{{x}−\sqrt{\left(\mathrm{1}−{x}\right){x}}+\mathrm{ln}\:\left(\sqrt{\mathrm{1}−{x}}+\sqrt{{x}}\right)}{\mathrm{2}}+{C} \\$$

Answered by mathmax by abdo last updated on 26/Apr/21

$$\mathrm{I}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\sqrt{\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}\mathrm{dx}\:\Rightarrow\mathrm{I}\:=_{\mathrm{x}=\mathrm{1}−\mathrm{t}} \:\:\:−\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\sqrt{\mathrm{1}−\mathrm{t}}}{\:\sqrt{\mathrm{1}−\mathrm{t}}+\sqrt{\mathrm{t}}}\left(−\mathrm{dt}\right) \\$$$$=\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\sqrt{\mathrm{1}−\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}\mathrm{dx}\:\Rightarrow\mathrm{2I}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \left(\frac{\sqrt{\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}+\frac{\sqrt{\mathrm{1}−\mathrm{x}}}{\:\sqrt{\mathrm{1}−\mathrm{x}}+\sqrt{\mathrm{x}}}\right)\mathrm{dx} \\$$$$=\int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{dx}\:=\mathrm{1}\:\Rightarrow\mathrm{I}\:=\frac{\mathrm{1}}{\mathrm{2}} \\$$$$\mathrm{there}\:\mathrm{is}\:\mathrm{atrick}\:\mathrm{in}\:\mathrm{this}\:\mathrm{integral}! \\$$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com